2012
DOI: 10.7314/apjcp.2012.13.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Overweight and Risk of Postmenopausal Breast Cancer: A Case-Control Study in Uruguay

Abstract: Obese postmenopausal women increase their risk of developing breast cancer (BC), in particular if they display an android-type pattern of adiposity, which is also associated to increased risks of diabetes mellitus, hypertension and cardiovascular disease. In order to explore the associations among anthropometry (body mass index, body composition, somatotype), some specific items of medical history (diabetes, hypertension, dislypidemias, hyperuricemia) and the risk of BC in Uruguayan women, a case-control study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 55 publications
1
30
0
2
Order By: Relevance
“…Formulas applied to calculate body composition and ST as well as additional details of the techniques were described in our recent paper on diabetes and overweight in postmenopausal BC (Ronco et al, 2012b).…”
Section: Body Composition and Somatotypementioning
confidence: 99%
“…Formulas applied to calculate body composition and ST as well as additional details of the techniques were described in our recent paper on diabetes and overweight in postmenopausal BC (Ronco et al, 2012b).…”
Section: Body Composition and Somatotypementioning
confidence: 99%
“…Populations differed regarding several risk factors and increased hormone concentrations were positively associated with body mass index (BMI; Chart 2) 38 . The study of Ronco et al was the only one that identified diabetes as a risk factor for BC (Chart 2) 42 . The authors determined the risk of diabetes in combination with overweight, high fat-to-muscle ratio and hypertension (Chart 2) 42 .…”
Section: Identified Risk Factors Of Bcmentioning
confidence: 99%
“…The study of Ronco et al was the only one that identified diabetes as a risk factor for BC (Chart 2) 42 . The authors determined the risk of diabetes in combination with overweight, high fat-to-muscle ratio and hypertension (Chart 2) 42 . In a similar study, Bering et al described a high prevalence of increased body mass index (BMI), high levels by Amadou et al 30 .…”
Section: Identified Risk Factors Of Bcmentioning
confidence: 99%
See 2 more Smart Citations